Maternal mortality in the UK: An update - Kemp, B; Knight, M (Elsevier, 2016)
The latest report of the United Kingdom Confidential Enquiry into Maternal Mortality, conducted by the MBRRACE-UK collaboration, was published in December 2014. The report has moved from triennial to annual publication with a chapter on each specific cause of maternal death included once every three years. In 2010-12, overall maternal mortality fell to 10.1 per 100,000 maternities; a 27% decrease compared to 2003-5. Whilst the maternal mortality rate from genital tract sepsis more than halved from its 20-year high in 2006-2008, sepsis per-se accounted for almost 25% of deaths. One in 11 of all deaths were associated with sepsis related to influenza, the majority 2009/A H1N1 influenza, which, in the presence of an effective vaccine, were largely preventable. The benefits of influenza vaccination should be promoted and women offered vaccination at any stage of pregnancy. Thrombosis was the leading cause of direct death, highlighting the ongoing importance of thromboprophylaxis.